Reversed‐phase HPLC enantioseparation of pantoprazole using a teicoplanin aglycone stationary phase—Determination of the enantiomer elution order using HPLC‐CD analyses - Papp Lajos Attila; Mohammadhassan Foroughbakhshfasaei; Fiser Béla; Bela Fiser; Фішер Бейло; Horváth Péter; Kiss Eszter; Khaled Sekkoum; Gyéresi Árpád; Hancu Gabriel; Noszál Béla; Szabó Zoltán‐István; et al. (Wiley-Liss, 2020)
Abstract. A direct HPLC method was developed for the enantioseparation of pantoprazole using macrocyclic glycopeptide‐based chiral stationary phases, along with various methods to determine the elution order without isolation of the individual enantiomers. In the preliminary screening, four macrocyclic glycopeptide‐based chiral stationary phases containing vancomycin (Chirobiotic V), ristocetin A (Chirobiotic R), teicoplanin (Chirobiotic T), and teicoplanin‐aglycone (Chirobiotic TAG) were screened in polar organic and reversed‐phase mode. Best results were achieved by using Chirobiotic TAG column and a methanol‐water mixture as mobile phase. Further method optimization was performed using a face‐centered central composite design to achieve the highest chiral resolution. Optimized parameters, offering baseline separation (resolution = 1.91 ± 0.03) were as follows: Chirobiotic TAG stationary phase, thermostated at 10°C, mobile phase consisting of methanol/20mM ammonium acetate 60:40 v/v, and 0.6 mL/min flow rate. Enantiomer elution order was determined using HPLC hyphenated with circular dichroism (CD) spectroscopy detection. The online CD signals of the separated pantoprazole enantiomers at selected wavelengths were compared with the structurally analogous esomeprazole enantiomer. For further verification, the inline rapid, multiscan CD signals were compared with the quantum chemically calculated CD spectra. Furthermore, docking calculations were used to investigate the enantiorecognition at molecular level. The molecular docking shows that the R‐enantiomer binds stronger to the chiral selector than its antipode, which is in accordance with the determined elution order on the column—S‐ followed by the R‐isomer. Thus, combined methods, HPLC‐CD and theoretical calculations, are highly efficient in predicting the elution order of enantiomers.
Editorial board: https://onlinelibrary.wiley.com/page/journal/1520636x/homepage/editorialboard.html
Contents: https://onlinelibrary.wiley.com/toc/1520636x/2020/32/2
Keywords: chiral separation; enantiorecognition; molecular modelling; omeprazole; online circular dichroism; pantoprazole; proton pump inhibitor; teicoplanine‐aglycone